1909. (21st April 2016) - Unknown
Abstract : Changeable day growing gloriously fine in the afternoon. Crowds of visitors on the lawn. Most successful party. To town in the afternoon to attend Stationers' Hall Banquet with H.S.H. Proposed toast of 'The New Livery'. Struck more than ever by the great beauty of the Hall and of the Court or drawing-room.